2018
DOI: 10.1186/s12871-018-0658-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of postoperative outcomes with PDA ligation in the OR versus the NICU: a retrospective cohort study on the risks of transport

Abstract: BackgroundAlthough patent ductus arteriosus (PDA) ligations in the Neonatal Intensive Care Unit (NICU) have been an accepted practice, many are still performed in the Operating Room (OR). Whether avoiding transport leads to improved perioperative outcomes is unclear. Here we aimed to determine whether PDA ligations in the NICU corresponded to higher risk of surgical site infection or mortality and if transport was associated with worsened perioperative outcomes.MethodsWe performed a retrospective cohort study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
(37 reference statements)
4
7
0
Order By: Relevance
“… 123 In a recent large multicenter retrospective study comparing PDA ligations in the operating room (OR) and the NICU, no differences in mortality or sepsis could be detected after correcting for differences in GA, besides an increased postoperative hemodynamic instability in the OR group. 124 Similar findings with no differences in mortality or complications after PDA ligation performed either in the OR or the NICU were presented in a 2-center retrospective cohort study from 2021, with a significantly earlier closure in the NICU group by 24 days. 125 …”
Section: Management Of Pdasupporting
confidence: 76%
See 2 more Smart Citations
“… 123 In a recent large multicenter retrospective study comparing PDA ligations in the operating room (OR) and the NICU, no differences in mortality or sepsis could be detected after correcting for differences in GA, besides an increased postoperative hemodynamic instability in the OR group. 124 Similar findings with no differences in mortality or complications after PDA ligation performed either in the OR or the NICU were presented in a 2-center retrospective cohort study from 2021, with a significantly earlier closure in the NICU group by 24 days. 125 …”
Section: Management Of Pdasupporting
confidence: 76%
“…123 In a recent large multicenter retrospective study comparing PDA ligations in the operating room (OR) and the NICU, no differences in mortality or sepsis could be detected after correcting for differences in GA, besides an increased postoperative hemodynamic instability in the OR group. 124 Similar findings with no differences in mortality or complications after PDA ligation performed either in the OR or the NICU were presented in a 2-center retrospective cohort study from 2021, with a significantly earlier closure in the NICU group by 24 days. 125 The difficulty to define early hsPDA and the trend toward a less aggressive approach to treat PDA surgically during the last decade, have shown that postponing surgical treatment of late hsPDA in cases of failed medical treatment is both feasible and even safer in terms of reduced severe neurodevelopmental impairment.…”
Section: Surgical Ligation: Bedside or Operating Theater?supporting
confidence: 76%
See 1 more Smart Citation
“…Although the 30-day mortality and perioperative (procedure related) hemodynamic instability were comparable between PDA ligation in OR (5% and 38.2% respectively) as reported by Lee et al . [ 28 ] and those in our series (4.5% and 32% respectively), transport-related problems such as hemodynamic instability during shifting to (5.6%) and from (12.4%) the OR and hypothermia (<36°C) in the intraoperative (26.3%) or postoperative (12%) period were noted in patients with OR ligations. Wang et al .…”
Section: Discussionsupporting
confidence: 53%
“…Most of the literature describing bedside surgery report advantages and safety for the patients involved 3,4 . The main contraindication for bedside surgery is the lack of a dedicated area.…”
Section: Introductionmentioning
confidence: 99%